Magic tree house : Thanksgiving on Thursday - Osborne, Mary Pope.; Murdocca, Sal. (New York : Random House, 2002)
Jack and Annie travel in their magic treehouse to the year 1621, where they celebrate the first Thanksgiving with the Pilgrims and Wampanoag Indians in the New Plymouth Colony.
590L
Decoding demand: 68 (high) Semantic demand: 90 (very high) Syntactic demand: 67 (high) Structure demand: 83 (very high)
Accelerated Reader AR
Keywords: Thanksgiving Day -- Fiction; Pilgrims (New Plymouth Colony) -- Fiction; Time travel -- Fiction; Historical fiction; Plymouth (Mass.) -- History -- 17th century -- Fiction; Fiction